Law students and entrepreneurship: A study on the relationship between involvement in entrepreneurship programs and interest to be entrepreneurs with special reference to IIUM - Abd Ghadas, Zuhairah Ariff; Muslim, Herna; Hamid, Zarinah (INSI Publications, 2012)
In Malaysia, the Government has been supportive in inculcating entrepreneurships skills at the higher learning institutions through policies such as training providers, funding, infrastructure and facilities to encourage students to start their own businesses (Mohd Zahari Ismail, 2006). Such support is seen as one of the effort to transform the country’s economy into a knowledge-based economy whereby entrepreneurship has been identified as one of the key elements to the development of the economy. It has been contended that in developing successful entrepreneurs, an early exposure in entrepreneurial courses is essential (Mansor and Othman, 2011). Law graduates in Malaysia are open to join either be the judiciary, government agencies, corporate and banking sectors or private practice. In most circumstances, law graduates will be attached to private firms and this eventually will lead to most of them opening their own legal firm. This means lawyers could not avoid standard business practices such as preparing cash flow report, business and succession plan and audit report. There are also many lawyers who end up in business, such as construction and trading companies. As such, law graduates are potential entrepreneurs. This paper intends to discuss the relationship between involvement in entrepreneurship programs and the interest of law undergraduates to become entrepreneurs when they graduated from the University. The study is based upon a survey conducted on law undergraduates of Ahmad Ibrahim Kulliyah of Laws, International Islamic University Malaysia (IIUM). A quantitative research methodology is adopted in this study.